3D analysis of transverse pipe–soil interaction using 2D soil slices. Issue 3 (23rd July 2013) - Byrne, B. W.; Martin, C. M.; Kong, D.
Abstract : Offshore pipelines are often laid directly on the seabed, particularly in deep water. Cyclic changes in the temperature and pressure of the pipe contents can lead to cyclic growth and contraction of (planned) lateral buckles. This results in severe plastic deformation of the near-surface soil as it is progressively scraped away and accumulated into berms by the lateral sweeping motion of the pipe. Quantifying the resistance offered by the soil is important in design, notably for fatigue calculations. This paper presents a new computational approach for modelling pipe–soil interaction during events dominated by large transverse pipe displacements. The main novelty is that a three-dimensional (3D) structural model of the pipe interacts with a series of discrete two-dimensional (2D) (plane strain) soil domains. Each 'slice' of soil is analysed using a coupled Eulerian–Lagrangian finite-element technique, though other large-displacement numerical methods could be employed. The concept is similar to recently developed macro-element approaches, except that the pipe–soil interaction at each (assumed) planar cross-section is captured by a 2D continuum model rather than by a 2D user-defined spring model. This is more efficient than a full 3D analysis of the pipeline and surrounding soil, yet it allows results of comparable accuracy to be obtained. This paper illustrates the new methodology with a simple calculation.